Woodworkig industries in Kharkiv Region during the NEP years:a historical aspect - Olianych, Valentina; Olianych, Larysa (My University, 2022)
The article examines the development of woodworking industries in Kharkiv region, the situation of artisans, their income and everyday life. The impact of the new economic policy on production volumes is determined. Cooperage, carpentry, and art products were studied. The transformation and development of handicrafts is identified and studied. The tax system that influenced woodworking handicraft production is considered. We made our own expedition to the workshop of a famous master who used the experience of his ancestors in the manufacture of products. The technology of production of wooden products characteristic of Kharkiv region is studied, and the industry concentration is determined. The connection of cooperage with other branches of agriculture is indicated. The authors studied the work of carpenters and described traditional housing of the hata-sena type and the gradual transformation in the Ukrainian village into a hata-sena-hata dwelling. We paid attention to the manufacture of tools (pitchforks, rakes), household items (troughs, mortars, ladles, buckets, etc.). The life of a rural family was directly connected with woodworking crafts, wood products were in demand, so the masters of this business increased significantly during the NEP period. The authors described the range of chiseled products, consisting of bowls, glasses, salt shakers, rolling pins. Birch, maple, hornbeam, and ash were used to make crafts. In the Slobozhansky Museum of local lore, at the exhibition "hall of ethnography", the authors studied wooden products and production technology of the period of the new economic policy in Kharkiv region.
Olianych V. Woodworkig industries in Kharkiv Region during the NEP years: a historical aspect / Valentina Olianych, Larysa Olianych, Andrzej Krynski // Scientific journal of polonia university, 2022. – № 4. – 83–89.
Keywords: селяни, бондарі, теслярі, сировина, сільські кустарі, селянська родина; peasants, coopers, carpenters, raw materials, rural artisans, peasant family